Comparison of AngularJS and React.js frameworks based on a web application - Capała, Łukasz; Skublewska-Paszkowska, Maria (Journal of Computer Sciences Institute, 2018)
The paper contains comparison between AngularJS and React.js frameworks. For research purposes two applications that provides the same functionalities were created. Time of typical tasks execution: elements insertion, sorting and deletion from JavaScript list of objects was measured and compared.